Tinjauan Yuridis Ratio Legis Syarat Usia Minumum Perkawinan Paska Putusan Mahkamah Konstitusi Nomor 22/PUU-XV/2017 - Fredy Alpin Gunawan; Indah Dwi Qurbani; Tunggul Anshari (Media Iuris, 2023)
AbstractMarriage aims to form a sakinah mawaddah warrahmah family, constitutionality issues arise when social problems occur as a result of early marriage and discriminatory differences between the age requirements of men and women. The Constitutional Court through its Decision 22/PUU-XV/2017 decided that the distinction was unconstitutional, and was ultimately followed up by the legislators. But in reality, there has been a surge in the volume of applications for dispensation for marriage, especially for women, because the age requirement has been increased. Therefore, this paper discusses: What is the ratio legis of the Marriage Law and its relationship to the development of regulations regarding the minimum age requirement for marriage? To answer that, normative research methods are used, with primary and secondary legal materials. Conclusion: The minimum age requirement for child marriage is experiencing social and legal developments. In the past, there were differences, through the Constitutional Court’s decision, finally, both men and women were equated with marriage. It is based on considerations of human rights law, particularly regarding the principle of non-discrimination based on gender. In fact, these changes have not been effectively implemented because there is a marriage dispensation instrument so that whoever submits it will surely be accepted by the court. Precisely with the addition of the minimum age requirement for marriage, it has an impact on the high volume of submissions for dispensation for marriage. AbstrakPerkawinan bertujuan membentuk keluarga sakinah mawaddah warrahmah, persoalan konstitusionalitas muncul ketika terjadi masalah sosial dampak dari pernikahan dini dan diskriminasi pembedaan antara syarat usia laki-laki dan perempuan. Mahkamah Konstitusi melalui Putusan 22/PUU-XV/2017 memutuskan bahwa pembedaan itu adalah inkonstitusional, dan akhirnya ditindakalnjuti oleh pembentuk undang-undang. Tetapi realitanya, justru terjadi lonjakan volume pengajuan dispenasasi kawin, khususnya perempuan lantaran syarat usianya dinaikan. Maka dari itu, tulisan ini membahas: Bagaimana ratio legis dari UU Perkawinan dan hubungannya dengan perkembangan pengaturan tentang syarat usia minimum perkawinan? Untuk menjawab itu, digunakan metode penelitian normatif, dengan bahan hukum primer dan sekunder. Disimpulkan: Syarat usia minimum perkawinan anak mengalami perkembangan sosial dan hukum. Dahulu terdapat perbedaaan, melalui putusan MK akhirnya keduanya disamakan antara pria dan wanita yang hendak melakukan perkawinan. Hal itu didasarkan pada pertimbangan hukum hak asasi manusia, khususnya mengenai prinsip non-diskriminasi berdasarkan gender. Dalam kenyatannya, perubahan tersebut tidak kunjung efektif dilaksanakan karena terdapat instrumen dispensasi kawin sehingga siapaun yang mengajukan pasti akan diterima oleh pengadilan. Justru dengan adanya penambahan syarat usia minimum perkawinan itu berdampak pada tingginya volume pengajuan dispensasi kawin.